Retronasal odor concentration coding in glomeruli of the rat olfactory bulb - Gautam, Shree Hari; Short, Shaina M.; Verhagen, Justus V. (Frontiers in Integrative Neuroscience, 2014)
The mammalian olfactory system processes odorants presented orthonasally (inhalation through the nose) and also retronasally (exhalation), enabling identification of both external as well as internal objects during food consumption. There are distinct differences between ortho- and retronasal air flow patterns, psychophysics, multimodal integration and glomerular responses. Recent work indicates that rats can also detect odors retronasally, that rats can associate retronasal odors with tastes, and that their olfactory bulbs (OBs) can respond to retronasal odorants but differently than to orthonasal odors. To further characterize retronasal OB input activity patterns, experiments here focus on determining the effects of odorant concentration on glomerular activity by monitoring calcium activity in the dorsal OB of rats using a dextran-conjugated calcium-sensitive dye in vivo. Results showed reliable concentration-response curves that differed between odorants, and recruitment of additional glomeruli, as odorant concentration increases. We found evidence of different concentration-response functions between glomeruli, that in turn depended on odor. Further, the relation between dynamics and concentration differed remarkably among retronasal odorants. These dynamics are suggested to reduce the odor map ambiguity based on response amplitude. Elucidating the coding of retronasal odor intensity is fundamental to the understanding of feeding behavior and the neural basis of flavor. These data further establish and refine the rodent model of flavor neuroscience.